The quick and easy performance appraisal phrase book : 3000+ powerful phrases for successful reviews, appraisals and evaluations - Alain, Patrick (Career Press, 2013)
"Have you ever found yourself at a loss for words around performance review time? Do you find yourself searching for the tone that will perfectly encapsulate exactly what you need to say to each employee? If so, The Quick and Easy Performance Appraisal Phrase Book is definitely for you! Whether you're a seasoned manager or just starting out, this is your go-to reference. Whether you need to jump-start the review-writing process or are searching for phrases you can use verbatim, The Quick and Easy Performance Appraisal Phrase Book features ready-made wording for virtually every situation. With this book, any manager will be able to quickly and easily select the best phrasing for any review--good or bad. The Quick and Easy Performance Appraisal Phrase Book contains more than 3,000 dynamic phrases that will help you: Say what needs to be said Take charge Boost your team's productivity Get the work done ... and done right! There is even a bonus section covering the "360 review," when employees review their managers! No matter who you are or what kind of review you need to write, this book will give you all the tools you need, right at your fingertips"--